1997
DOI: 10.1080/03014469700004852
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of body composition measures and menstrual cycle length

Abstract: Menstrual cycle disruption has been observed in women with low body weight due to anorexia nervosa, or to athletics. However, the association of the full range of body composition measures with cyclicity has not been determined. Therefore, the purpose of this study was to determine the strength and direction of association between body composition measures (Quetelet Index, body fat mass, and body lean mass) and menstrual cycle length. Menstrual cycle diaries were distributed to women aged 24-45 in the Michigan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
3
26
1
Order By: Relevance
“…In previous studies, extremes of weight have been associated with the risk of long, irregular, 8,[32][33][34] and anovulatory cycles 6,34 typical of polycystic ovarian syndrome. Moderate overweight has been associated with ovulatory disorder infertility in the NHS-II cohort 17,35 and others.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, extremes of weight have been associated with the risk of long, irregular, 8,[32][33][34] and anovulatory cycles 6,34 typical of polycystic ovarian syndrome. Moderate overweight has been associated with ovulatory disorder infertility in the NHS-II cohort 17,35 and others.…”
Section: Discussionmentioning
confidence: 99%
“…D. Harlow, Campbell, Lin, & Raz, 1997;S. D. Harlow & Campbell, 1994;Matteo, 1987;Rowland et al, 2002;Symons, Sowers, & Harlow, 1997) Although the literature on stress and reproductive function has principally focused on ovarian aging and menopause, a number of earlier studies looked at the relationship between stress and menstrual cycle characteristics. For example, Matteo (Matteo, 1987) and Harlow and Matanoski (S. D. Harlow & Matanoski, 1991) each found that self-reported measures of stress correlated with longer menstrual cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Symons et al 26 determined the degree of association between body-composition measures (Quetelet Index, lean body mass, and fat body mass) and menstrual cycle length by analyzing diaries from 436 women (aged 24-45 years) encompassing 4392 menstrual cycles. Mean cycle length, variability of cycle length, and mean bleeding length were calculated from those diaries.…”
Section: Discussionmentioning
confidence: 99%
“…Both body mass and body composition are associated with menstrual function; the probability of dysfunction is greater among women with either a low or high body mass index (BMI). 9,[25][26][27] Among reproductiveaged women, those with the longest mean cycle lengths had greater BMI, lean body mass, and fat body mass, but women in the lowest decile of BMI and fat body mass also had long mean cycle lengths. 26 Studies 3,9,26,28 of athletes and the general population have consistently shown that individuals with highly variable cycles or amenorrhea tend to weigh less, to have a lower percentage of body fat, and to report more weight loss than women with normal menstrual cycles do.…”
Section: Endocrinology Of Physical Activity and Menstrual Cyclicitymentioning
confidence: 99%
See 1 more Smart Citation